2022
DOI: 10.1016/j.prdoa.2022.100130
|View full text |Cite
|
Sign up to set email alerts
|

The potential role of the cardiac MIBG scan in differentiating the drug-induced Parkinsonism from Parkinson’s disease

Abstract: Highlights MIBG scan is more positive in the PD group than the DIP. There is a significant difference in MIBG uptake between the PD and DIP groups. MIBG scan can be used to determine the prognosis of DIP. MIBG scan is 84.4% sensitive and 86.36% specific in diagnosing PD. MIBG scan is useful in better referring the patients to related centers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Moreover, Shafie et al reported that [123I]-MIBG scans could be used to determine the prognosis of people with parkinsonism secondary to drugs. The subjects with drug-induced parkinsonism that did not improve motor symptoms after offending drug discontinuation had a low heart-to-mediastinum ratio [95].…”
Section: [123i]-mibg Cardiac Imagingmentioning
confidence: 96%
“…Moreover, Shafie et al reported that [123I]-MIBG scans could be used to determine the prognosis of people with parkinsonism secondary to drugs. The subjects with drug-induced parkinsonism that did not improve motor symptoms after offending drug discontinuation had a low heart-to-mediastinum ratio [95].…”
Section: [123i]-mibg Cardiac Imagingmentioning
confidence: 96%
“… 2 This pathophysiology clinically manifests through common motor symptoms, including resting tremor, bradykinesia, gait difficulties, muscle rigidity, and postural instability, which interferes with activities of daily living. 3 , 4 Although PD is mainly known by motor symptoms, many nonmotor symptoms (NMS) are proposed to be associated with PD. Importantly, motor symptoms are usually associated with the advanced disease, while NMS could be utilized as early biomarkers of the disease even before the diagnosis of PD.…”
Section: Introductionmentioning
confidence: 99%
“…As one of the most common progressive neurodegenerative disorders worldwide, mainly among the elderly population, Parkinson's disease (PD) is characterized by piecemeal loss and death of the substantia nigra pars compacta neurons and aggregation of the α‐synuclein (α‐syn) protein in the central nervous system 2 . This pathophysiology clinically manifests through common motor symptoms, including resting tremor, bradykinesia, gait difficulties, muscle rigidity, and postural instability, which interferes with activities of daily living 3,4 . Although PD is mainly known by motor symptoms, many nonmotor symptoms (NMS) are proposed to be associated with PD.…”
Section: Introductionmentioning
confidence: 99%
“…As one of the most common progressive neurodegenerative disorders worldwide, chie y among the elderly population, Parkinson's disease (PD) is characterized by piecemeal loss and death of the substantia nigra pars compacta neurons and aggregation of the alpha-synuclein protein (α-syn) in the central nervous system (2,3). This pathophysiology clinically manifests through common motor symptoms, including resting tremor, bradykinesia, gait di culties, muscle rigidity, and postural instability, which interferes with activities of daily living (4). However, although PD is mainly known by motor symptoms, many non-motor symptoms (NMS), ranging from sensory abnormalities, cognitive impairment, sleep disturbances (insomnia, REM sleep behavior disorder (RBD), Excessive daytime sleepiness, painful dystonia), autonomic dysfunction (orthostatic hypotension, obstipation), psychosis are proposed to be correlated with PD (4).…”
Section: Introductionmentioning
confidence: 99%
“…This pathophysiology clinically manifests through common motor symptoms, including resting tremor, bradykinesia, gait di culties, muscle rigidity, and postural instability, which interferes with activities of daily living (4). However, although PD is mainly known by motor symptoms, many non-motor symptoms (NMS), ranging from sensory abnormalities, cognitive impairment, sleep disturbances (insomnia, REM sleep behavior disorder (RBD), Excessive daytime sleepiness, painful dystonia), autonomic dysfunction (orthostatic hypotension, obstipation), psychosis are proposed to be correlated with PD (4).…”
Section: Introductionmentioning
confidence: 99%